2015
DOI: 10.14202/vetworld.2015.217-220
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Brucella abortus and Leptospira hardjo in cattle

Abstract: Aim:The aim was to assess the seroprevalence of B. abortus and Leptospira hardjo in the cattle population of Bihar, this work was carried out.Materials and Methods:Randomly selected 450 cattle from nine districts of Bihar were serologically screened for antibodies against L. hardjo and B. abortus. DAS-ELISA for leptospira and AB-ELISA for brucella were carried out. Based on the results prevalence in each district and the state are reported herewith.Results and Discussion:In this study, it was found that the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…There are various researchers who reported management wise prevalence of bovine brucellosis in India. In this study, the results coincided with the findings of Isloor et al [26][27][28] showing that a higher prevalence of brucellosis was observed in organized farms than in single cow herds. This may be attributed to the spread of infection that is quick, easily spread and mainly due to the improper screening, surveillance and monitoring.…”
Section: Husbandry Practices-wise Prevalence Of Bovine Brucellosis Bysupporting
confidence: 92%
“…There are various researchers who reported management wise prevalence of bovine brucellosis in India. In this study, the results coincided with the findings of Isloor et al [26][27][28] showing that a higher prevalence of brucellosis was observed in organized farms than in single cow herds. This may be attributed to the spread of infection that is quick, easily spread and mainly due to the improper screening, surveillance and monitoring.…”
Section: Husbandry Practices-wise Prevalence Of Bovine Brucellosis Bysupporting
confidence: 92%
“…An earlier study conducted in 23 states of India reported an overall sero-prevalence of 3.5% in Bihar [ 16 ]. A few other studies have reported even higher seropositivity in Bihar (12.2% by Pandian et al [ 17 ] and 9.3% by Kaushik et al [ 18 ]). These findings were contrary to our study results.…”
Section: Discussionmentioning
confidence: 97%
“…There are reports that prevalence in organized dairy farms is typically higher than in marginal herds [18,19,22,38,39]. This higher prevalence in organized dairy farms may be due to higher prevalence of the disease in exotic and cross-bred animals, compared to indigenous cattle [40], transmission of disease during natural mating/artificial insemination, physical contact because of close confinement and exposure to diseased animals [18,22]. On the contrary, a few studies reported significantly lower prevalence in organized farms than marginal herds possibly because of proper management, good sanitation and disinfection, proper disposal of placenta, better animal health awareness and management and vaccination; however, the number of these types of farms where studies were conducted were few and not representative of organized farms overall [17,33].…”
Section: Risk Factorsmentioning
confidence: 99%